GE_GERICHTE P/26167/2022 vom 15. Dezember 2023 - GE Cour de justice (2023)
DOMMAGE;PRÉVENU;PROCÉDURE PÉNALE;SÉQUESTRE(MESURE PROVISIONNELLE);COMPTE BANCAIRE;PRÊT DE CONSOMMATION | CPP.429; CPP.263; CPP.266